IN VITRO ANTIMICROBIAL PROPERTIES OF HEDYSARUM ANATOLICUM EXTRACTS - Atif Abdulazeez Khudur; Aylan arslan ali; Tuna UYSAL; Ela Nur smisek SEZER (Scholar Express Journals, 2021)
The genus Hedysarum belongs to the Fabaceae family and is represented by a total of 22 species, 12 of which are endemic in our country. Hedysarum anatolicum is an endemic species that naturally spread in our country. In this study, the antimicrobial effects of methanolic extracts obtained from Hedysarum anatolicum leaves and flowers were tried to be revealed. Eight different concentrations of each extract were used against seven clinically isolated bacterial strains (Staphylococcus aureus, Escherichia coli, Enterobacter cloacae, Streptococcus pyogenes, Pseudomonas aeruginosa, Klebsiella pneumonia, Burkholderia cepaciae) and a fungus (Candida albicans). The agar well diffusion technique was used to determine the antimicrobial activity of the extracts. As a result, it was determined that both extracts inhibited bacterial growth at different concentrations. Based on the inhibition zone in Streptococcus pyogenes, it was determined that the antibacterial activity of the extract was higher than that of antibiotics on some bacterial species. In conclusion, antimicrobial potential of the extracts obtained from H. anatolicum was revealed with this study.
Keywords: Inhibition zone; Hedysarum; Turkey